Chloroquine Improves Deoxynivalenol-Induced Inflammatory Response and Intestinal Mucosal Damage in Piglets. (10th June 2020) - Liao, Simeng; Tang, Shengguo; Tan, Bie; Li, Jianjun; Qi, Ming; Cui, Zhijuan; Zha, Andong; Wang, Yanan; Yin, Yulong; Sun, Peng; Tang, Yulong
Abstract : We investigated the effects of rapamycin (RAPA) and chloroquine (CQ) in supporting growth performance and the intestinal mucosal barrier in response to deoxynivalenol (DON) in piglets. A total of 32 healthy weaned piglets (bodyweight 7.10 ± 0.58   kg ) were divided into four groups and treated daily with RAPA (1 mg/kg BW), CQ (10 mg/kg BW), or a control volume of normal saline (two groups) until the end of the experiment. After feeding a basal diet for seven days, three groups were then switched to mildewed feed containing 1 mg kg/DON for a further seven days. In contrast to the control group, DON-treated piglets showed decreased average daily gain (ADG) and daily feed intake (ADFI), as well as negatively affected intestinal morphology as indicated by villus height, crypt depth, and tight junction protein expression. A group treated with RAPA and DON showed increased intestinal autophagy, aggravated inflammatory responses, and damage to the intestinal mucosa and permeability, leading to reduced growth performance. Meanwhile, a group treated with CQ and DON showed indices comparable to the non-DON control group, with alleviated inflammatory cytokines and healthy intestinal morphology and structure. They also showed better growth performance compared to DON treatment alone. These findings have important implications for mediating autophagy against DON in vivo, as well as the potential for CQ in improving growth performance and maintaining intestinal barrier integrity in weanling piglets.